Ilizarov bone transport for the treatment of segmental tibial bone defect - Mohd Yusof, Nazri; Sulong, Ahmad Fadzli; Nik Abdul Adel, Nik Alyani (2019)
Segmental Tibial bone defect is challenging because of its poor soft tissue coverage. Reconstruction using internal fixation carry a risk of infection. Furthermore, large segmental defect often require large amount of autologous bone graft. However, ilizarov bone transport is a complex reconstruction procedure that is associated with a lot of complications and treatment failures. The aim of this study is to review the outcome of patients treated for segmental tibial defect in Advanced Trauma and Limb Reconstruction Unit in our hospital. Methodology This is a retrospective study of 36 patients who have underwent bone transport from January 2006 to December 2018. There were 32 males and 4 females with a mean age of 33.2 years old (range 15 to 65). Fifteen defect in the distal, 13 midshaft and 8 proximal tibia. Nineteen cases due to open fractures, 9 implant related infection, 3 atrophic non-union, 3 septic non-union and 2 osteomyelitis. Four patients have underlying diabetes mellitus, 1 HIV and 1 hepatitis B infection. Fifteen patients had a local flap and 1 had a free flap surgery to cover the soft tissue defect. The mean size of bone defect is 4.8 cm (range 2- 10 cm). The clinical and functional status was assessed using the ASAMI criteria. Results Two patients were not able to complete the treatment because cannot tolerate the ilizarov external fixation. Thirty (88%) patients achieve union with a meant time of 12 months (range 5 to 30 month). Four patients develop non-union. Two underwent amputation, 1 free fibular transfer and 1 underwent bone transport with the Monorail external fixation. Twenty three achieve excellent, 4 good and 3 fair bone results. Eleven achieve excellent, 17 good and 1 each fair and poor functional results. Conclusions Ilizarov bone transport able to salvage nearly 90% of segmental tibial defect with more than 90% excellence and good functional results. Patients’ selection and close monitoring are important to achieve successful treatment.